Urban archetypes applied to the study of cities in historic contemporary fictions. Symbolic urban structures in Age of Empires III and Bioshock Infinite - Manuel Sánchez García (Culture & History Digital Journal, 2020)
In “The Idea of a Town: Anthropology of Urban Form” (1976), architecture historian Joseph Rykwert defined six archetypes used in Etruscan rites for the foundation of urban settlements, which continued to be used in Classical Greece and Ancient Rome. He proposed to use these same categories for the study of cities in different eras, as a methodology to develop a global urban history. This paper projects Rykwert’s concepts to cities created during the XXI century, specifically those designed for video games with historical themes, and provides the reader with an experimental methodology for assessing digital architectures and environments. Spatial and narrative archetypes will be identified in two different video games, as well as their connections to imaginaries born in the Classic period. In Age of Empires (Ensemble Studios, 1996-2005) urban foundation corresponds to the idea of the town as a place for dominating territory. Their variable structure is grounded on a systemic set of rules that benefits tactic configurations designed by players. In contrast, Bioshock Infinite (Irrational Games, 2013) proposes an immobile storyline built around the city as its leading narrative voice. Its urban spaces direct the action through archetypes such as the “center”, the “labyrinth”, and the “door”.